Cognitive factors explain inter-cultural variations of abilities in rhythm perception: The case of the Roma minority. (September 2019) - Dolean, Dacian Dorin; Tincas, Ioana
This study aimed to determine what role cognitive factors play in inter-cultural variations of rhythm perception and to assess whether the stereotype of enhanced musical abilities in the Roma minority is supported by empirical evidence. The rhythm perception of 487 Roma and non-Roma children was assessed comparatively, while controlling for cognitive skills. Contrary to popular belief, the rhythm perception of Roma children was lower than that of their non-Roma peers; however, this difference in performance was explained fully by cognitive variables. The results indicate that further comparative investigations of rhythm perception across cultures should account for cognitive factors, and that the reported enhanced musical ability of the Roma minority is a stereotype that is not supported by empirical evidence.